Association of Monocyte-to-HDL Cholesterol Ratio with Endothelial Dysfunction in Patients with Type 2 Diabetes - Huihui Zhang; Jun Lu; Jie Gao; Wenjun Sha; Xinhua Cai; Mai Re Yan Mu Rouzi; Yuanying Xu; Wenjun Tang; Tao Lei (Journal of Diabetes Research)
Aims. To explore the relationship between monocyte-to-HDL cholesterol ratio (MHR) and endothelial function in patients with type 2 diabetes (T2DM). Methods. 243 patients diagnosed with T2DM were enrolled in this cross-sectional study. Patients were divided into two groups by flow-mediated dilation (FMD) quintile as nonendothelial dysfunction (FMD≥6.4%) and endothelial dysfunction (FMD<6.4%). The relationship between MHR and FMD was analyzed using Spearman’s correlation, partial correlation, and multiple logistic regression analysis. ROC curve was fitted to evaluate the ability of MHR to predict endothelial dysfunction. Results. Endothelial dysfunction was present in 193 (79%) patients. Patients with endothelial dysfunction had higher MHR (p<0.05) than those without endothelial dysfunction. Furthermore, MHR had a significantly positive correlation with endothelial dysfunction (r=0.17, p<0.05), and the positive association persisted even after controlling for confounding factors (r=0.14, p<0.05). Logistic regression showed that MHR was an independent contributor for endothelial dysfunction (OR: 1.35 (1.08, 1.70), p<0.05) and the risk of endothelial dysfunction increases by 61% with each standard deviation increase in MHR (OR: 1.61 (1.12, 2.30), p<0.05) (model 1). After adjusting for sex, age, BMI, disease course, hypertension, smoking, and drinking (model 2) as well as HbA1c, HOMA-IR, C-reactive protein, and TG (model 3), similar results were obtained. In ROC analysis, the area of under the ROC curve (AUC) for MHR was 0.60 (95% CI 0.52-0.69, p<0.05). Conclusion. MHR was independently associated with endothelial dysfunction in T2DM patients. It could be a new biomarker for vascular endothelial function assessment.